The effect of different fluoride varnishes on the release of calcium ions from hydroxyapatite discs: An ion-selective electrodes study - Kamarudin, Aimi; Anderson, Paul; Hill, Robert (Faculty of Dentistry Universitas Padjadjaran, 2020)
Introduction: Recently, various modes of fluoride varnishes have evolved, each with its own recommended concentration, potentially active ingredients, and flavour, leading to a claim of additional preventive benefits. Differences in fluoride release patterns can potentially enhance or reduce the efficacy of fluoride varnishes. Numerous clinical trials have proven its ability in preventing and arresting dental caries. This study mainly focused on the investigations of the apatite demineralisation process under the effect of different fluoride varnishes by ion-selective electrodes (ISE), in an attempt to comprehend their mechanism in anti-caries. Methods: Four different fluoride varnishes (Fluor Protector S, Duraphat, ClinPro White, MI Varnish) were used to measure their effect on the demineralisation process of the hydroxyapatite (HAP) discs in 60ml pH 4.0 acetic solutions. The HAP discs were treated with these varnishes after 4-hours demineralisation and then immersed back into the same solutions for further demineralisation to observe the effect of the varnishes. Throughout the experiment, the calcium ISE was used to monitor the rate of calcium concentration. Results: The result demonstrated that ClinPro White varnish resulted in the most significant inhibition of demineralisation and signs of probable remineralisation throughout the experiment. Other fluoride varnishes treatment showed the ability to inhibit demineralisation. However, the rate of calcium dissolution was not significantly different from different varnishes. The fact that the ClinPro White showed evidence of remineralisation might be associated with the fact that the varnish contained a source of calcium and phosphate. Conclusion: The fluoride varnishes treatment is shown to be effective in inhibiting the demineralisation of apatite regardless of the difference in fluoride concentration and potentially active ingredients incorporated in some of the fluoride varnishes.